Pelaksanaan (Problem Based Learning) Sebagai Metode Untuk Meningkatkan Hasil Belajar Bahasa Inggris Di SMAN 9 Rejang Lebong - Tiarahma Pusparila (Lembaga Bale Literasi, 2022)
The purpose of this study was to determine and evaluate the ability of the PBL model to improve English learning outcomes. In the Problem Based Learning (PBL) implementation model, students form several small groups to work together to solve a problem or problem related to the subject that has been agreed upon between the teacher and students. Since student performance has been very low in recent years, a solution must be found. As a result, as many as 28 students of class XI IPA 1 at SMAN 9 Rejang Lebong took part in classroom action research during semester 2 of the 2020/2021 school year. The results of learning English are the subject of research. Data was collected using a learning achievement test and analyzed descriptively qualitatively. If the average value of this action research is at least 70 and the classical learning completeness is at least 85 percent, then it is considered successful. Based on the research findings, the average value of the first cycle was 69.41, and classical completeness was 78.94%. In contrast, in cycle II, classical completeness reached 89.47 percent and the average value was 72.88. Semester 1 of the 2020/2021 academic year the Problem Based Learning model can improve student learning outcomes in class XI IPA 1 at SMAN 9 Rejang Lebong.